Cognitive function and physical performance in young adults who had and had not experienced the COVID-19 infection - Suphannika Ladawan; Patchareeya Amput; Saisunee Konsanit; Patcharin Phrompao (International Journal of Adolescence and Youth)
The aim of the present study is to compare the cognitive function and physical performance of young adults who have experienced the COVID-19 infection with those who have not. Twenty-one participants who had experienced the COVID-19 infection and 21 non-COVID controls underwent a cognitive assessment (Digit Span Forward Test: DSF, and Stroop Colour and Word Test: SCWT) and physical performance test (six-minute walk test: 6MWT). The participants in the COVID-19 group tended to have lower cognitive and physical performance than those in the control group. However, the difference was not statistically significant (DSF: p = 0.59, SCWT- Word: p = 0.18, SCWT- Color: p = 0.73, SCWT-Colour – Word t: p = 0.14, and 6MWT: p = 0.54). The cognitive function and physical performance in post-COVID-19 young adults tended to be lower than non-COVID-19 participants but failed to reach statistical significance. Further studies, particularly involving large sample sizes, are required to confirm the effect of COVID-19 in young adults.